Euroregiony jako płaszczyzna współpracy i integracji - rozważania teoretyczne - Koszyk-Białobrzeska, Renata; Zabielska, Izabela (Euroregions as a Form of Co-Operation and Integration - Theoretical Considerations, 2009)
The paper aims at presenting the major reasons for initiation of crossborder co-operation in euroregions. Euroregions create conditions for social and economic stimulation of border areas. They offer opportunities for overcoming the negative consequences of marginal location and isolation of those areas.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 663-669